2023
DOI: 10.1007/s11146-023-09945-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of House Price on Economic Stability: Some Lessons from OECD Countries

Abstract: Despite having abundant literature blaming a faulty financial system and exuberant‎ price expectations as the primary causes of housing bubbles, there is a lack of research that looks at the impact of house price instability on the economy. This study aims to fill this gap by thoroughly examining the connection between house prices and economic output, and the effect of house price volatility on economic stability. Drawing from long-spanning quarterly data from 17 OECD countries from 1970 to 2019, the study de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…This is because, in wornout urban textures, the decrease in construction activities has had a negative effect on the production and supply of residential units while simultaneously driving up housing prices. As Asadov et al (2023) point out, a decrease in investment can have a negative impact on economic growth. They demonstrated that fluctuations in housing prices can significantly influence economic fluctuations, which may adversely affect long-term economic growth and housing prices.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…This is because, in wornout urban textures, the decrease in construction activities has had a negative effect on the production and supply of residential units while simultaneously driving up housing prices. As Asadov et al (2023) point out, a decrease in investment can have a negative impact on economic growth. They demonstrated that fluctuations in housing prices can significantly influence economic fluctuations, which may adversely affect long-term economic growth and housing prices.…”
Section: Conclusion and Discussionmentioning
confidence: 99%